1996
DOI: 10.1111/j.1559-1816.1996.tb01127.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnic Hierarchy Among Majority and Minority Youth In The Netherlands

Abstract: This study tests the hypothesis that ethnic groups have consensus about the relative position of ethnic out‐groups in society. A survey among ethnic majority and minority youth in the city of Rotterdam indicated that: (a) each ethnic group preferred the in‐group, (b) there was consensus on an ethnic hierarchy within ethnic groups, and (c) ethnic groups largely agreed on the ethnic rank order. Among the Dutch respondents, the ethnic hierarchy was found to be related to real cultural differences. The scheme of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 17 publications
8
66
0
1
Order By: Relevance
“…A higher perceived cultural distance has been associated with a higher ethnic and lower mainstream orientation (Schachner et al, in press). Cultural distance and ethnic hierarchy were also found to already underlie intergroup relations amongst minority and majority early adolescents (Schachner et al, 2015;Verkuyten et al, 1996) and even children, with those from lower ranking groups reporting higher levels of peer discrimination (Verkuyten, 2002). In their integrative model of child development, García Coll and colleagues García Coll & Szalacha, 2004) suggest that the social status of a child's ethnic group in a society is one of the most important factors in predicting psychological and developmental outcomes.…”
Section: Conditions For Acculturation and Adjustment Related To Ethnimentioning
confidence: 99%
See 1 more Smart Citation
“…A higher perceived cultural distance has been associated with a higher ethnic and lower mainstream orientation (Schachner et al, in press). Cultural distance and ethnic hierarchy were also found to already underlie intergroup relations amongst minority and majority early adolescents (Schachner et al, 2015;Verkuyten et al, 1996) and even children, with those from lower ranking groups reporting higher levels of peer discrimination (Verkuyten, 2002). In their integrative model of child development, García Coll and colleagues García Coll & Szalacha, 2004) suggest that the social status of a child's ethnic group in a society is one of the most important factors in predicting psychological and developmental outcomes.…”
Section: Conditions For Acculturation and Adjustment Related To Ethnimentioning
confidence: 99%
“…This is called the "ethnic hierarchy" in a particular society. The ethnic hierarchy in a country also seems to be perceived by members of minority groups, and groups at the bottom are typically also rejected by other, higher ranking minority groups (Verkuyten, Hagendoorn, & Masson, 1996).…”
Section: Conditions For Acculturation and Adjustment Related To Ethnimentioning
confidence: 99%
“…An ordinal conception of ethnicity manifests itself in a hierarchy of ethnic groups in terms of social distance from the Dutch majority (Hraba, Hagendoorn, & Hagendoorn, 1989). Several studies have found consensus on the hierarchy of ethnic groups in The Netherlands (e.g., Hraba et al, 1989;Verkuyten, Hagendoorn, & Masson, 1996) where European groups were placed on top, followed by colonial and then Islamic groups at the bottom. More specifically, the following hierarchy is used (Hraba et al, 1989): (a) Dutch majority, (b) Western ethnic minority (which includes people from Western and Eastern Europe, and Western non-European countries), (c) Caribbean, (d) Surinam, (e) Morocco, and (f) Turkey.…”
Section: Analysesmentioning
confidence: 99%
“…Many authors (Clark and Ayers, 1992;DuBois and Hirsch, 1990;Patchen, 1982;Schofield, 1979Schofield, , 1982Schofield, , 1986Verkuyten et al, 1996) have studied in-group and out-group preferences. However, preferences for relationships can be very different from reality: natives (Dutch and/or Flemish) may indicate that they are interested in engaging in inter-ethnic friendships without having them.…”
Section: Ethnic Boundariesmentioning
confidence: 99%